Handbook of biologically active peptides - Kastin, Abba J. (Elsevier/Academic Press, 2013)
"Peptides play a crucial role in many physiological processes including actions as neurotransmitters, hormones, and antibiotics. Research has shown their importance in such fields as neuroscience, immunology, pharmacology, and cell biology. The Handbook of Biologically Active Peptides presents, for the first time, this tremendous body of knowledge in the field of biologically active peptides in one single reference. The section editors and contributors represent some of the most sophisticated and distinguished scientists working in basic sciences and clinical medicine. The Handbook of Biologically Active Peptides is a definitive, all-encompassing reference that will be indispensable for individuals ranging from peptide researchers, to biochemists, cell and molecular biologists, neuroscientists, pharmacologists, and to endocrinologists. Chapters are designed to be a source for workers in the field and will enable researchers working in a specific area to examine other related areas with which they would not ordinarily be familiar"--Publisher's description.